Attitudes toward singlehood, negative stereotyping of single persons and perceived control as determinants of intention to be single among young adults in Malaysia - Chong, Joanne Hui Qi; Leong, Wen Sam; Leow, Rou Yi (2022)
Singlehood has become increasingly prevalent among young adults as emerging adulthood is considered as a period of development that could lead to individuals concentrating more on different life domains - thus increasing the tendency to be single. However, there are limited studies that focus on understanding of the intention to be single. The present study investigated the relationship between attitudes toward singlehood, negative stereotyping of single persons, perceived control and intention to be single among young adults in Malaysia by using the theory of planned behaviour (TPB). A quantitative cross-sectional study was conducted online on Malaysian young adults aged between 20 to 29 years old who were currently single. Purposive sampling method was used to recruit a total of 417 participants. The variables of this study were measured by using Attitudes Toward Singlehood Scale (AtSS), Negative Stereotyping of Single Persons Scale (NSSP), Sense of Control Scale (SC), and Intention to be Single Scale (ITS). By using Multiple Linear Regression to analyse the findings, the attitudes toward singlehood and negative stereotyping of single persons were positively related to the intention to be single whereas perceived control was negatively related to the intention to be single among young adults in Malaysia. In conclusion, this study has extended the use of TPB in the context of singlehood and the findings could contribute to the development of social policy in Malaysia through understanding the determinants of the intention to be single.